TRANSMISI KEBIJAKAN MONETER JALUR PEMBIAYAAN BANK SYARIAH DI INDONESIA - Imronjana Syapriatama (UIN Mataram, 2017)
This research aims to examine the role of Sharia Banks on the financingchannel monetary transmission mechanism in Indonesia. Using data fromJanuary 2014 – December 2016, this study applies Vector Error CorrectionModel (VECM). Variables that represent sharia banking are third partyfund (DPK) dan financing (FIN). Variable that represents monetary policyis rate of Central Bank Sharia Certificate (SBIS) and monthly economicgrowth proxied by Industrial production Index (IPI). This research showsthat monetary policy and sharia bank have significant influence toward theeconomic growth, while monetary policy has no impact to sharia bankreserves. This result indicates that sharia banks are not affected to thechanges of Bank Indonesia monetary policy